ESSAY AS ONE OF THE TYPES OF GENRE OF LITERATURE - С. Р. Шейхмамбетов (Web of Journals Publishing, 2024)
The article discusses several general tips for writing texts of various types. And also the development of writing skills has many positive consequences for cognitive processes and volitional qualities.
Keywords: persuasion, outlook, informing, description, analysis, complexity, perseverance, essay, patience, self-discipline, articulation of thoughts, choice of words, argumentation, reflect.